Analisis Pengaruh Kepemimpinan, Budaya Kerja, dan Sarana Prasarana terhadap Prestasi Siswa - Saaduddin Saaduddin (Journal on Education, 2021)
In order to help liberate society from ignorance and backwardness which result in low quality human resources, education plays a very important role. In improving the quality of education, it is necessary to carry out quality assurance in accordance with standards, norms, criteria and guidelines for implementing national education. The aim of the research was to determine the influence of leadership factors, culture of activities, and on student achievement, and to determine the most dominant factors influencing learning achievement. This research took place at MAN 1 Kerinci. The number of samples taken in this study were 100 respondents from 240 populations selected through the sampling technique, namely random sampling. In this study, binary logistic regression was used. The accuracy test of the regression model used to assess the accuracy of the regression model in this study was measured by the chi-square value using the Hosmer and Lemeshow tests. Based on the results of the binary logistic regression analysis, it was obtained that the independent variables consisting of leadership, activity culture, and offerings had a positive and significant relationship with proven student learning achievement with a sig value on the third variable entirely <0.05. Of the three independent variables in cultural reality representing the most dominant factor activity variable, this is evidenced by the results of the B or Exp (B) skill test of 2.683, and a beta coefficient value of 0.987 which is actually greater than the other variables. The results of the study explained that based on the results of binary logistic regression analysis it was found that the independent variables consisting of leadership, work culture, and infrastructure had a positive and significant effect on student achievement.